Expression analysis suggests that DNMT3L is required for oocyte de novo DNA methylation only in Muridae and Cricetidae rodents - Behluli, Lirik; Fontanilla, Alyssa M.; Andessner-Angleitner, Laura; Tolar, Nikolas; Molina, Julia M. [UNESP]; Gahurova, Lenka (Springer Nature, 2023)
Background: During early mammalian development, DNA methylation undergoes two waves of reprogramming, enabling transitions between somatic cells, oocyte and embryo. The first wave of de novo DNA methylation establishment occurs in oocytes. Its molecular mechanisms have been studied in mouse, a classical mammalian model. Current model describes DNA methyltransferase 3A (DNMT3A) and its cofactor DNMT3L as two essential factors for oocyte DNA methylation—the ablation of either leads to nearly complete abrogation of DNA methylation. However, DNMT3L is not expressed in human oocytes, suggesting that the mechanism uncovered in mouse is not universal across mammals. Results: We analysed available RNA-seq data sets from oocytes of multiple mammals, including our novel data sets of several rodent species, and revealed that Dnmt3l is expressed only in the oocytes of mouse, rat and golden hamster, and at a low level in guinea pigs. We identified a specific promoter sequence recognised by an oocyte transcription factor complex associated with strong Dnmt3l activity and demonstrated that it emerged in the rodent clade Eumuroida, comprising the families Muridae (mice, rats, gerbils) and Cricetidae (hamsters). In addition, an evolutionarily novel promoter emerged in the guinea pig, driving weak Dnmt3l expression, likely without functional relevance. Therefore, Dnmt3l is expressed and consequently plays a role in oocyte de novo DNA methylation only in a small number of rodent species, instead of being an essential pan-mammalian factor. In contrast to somatic cells, where catalytically inactive DNMT3B interacts with DNMT3A, forming a heterotetramer, we did not find evidence for the expression of such inactive Dnmt3b isoforms in the oocytes of the tested species. Conclusions: The analysis of RNA-seq data and genomic sequences revealed that DNMT3L is likely to play a role in oocytes de novo DNA methylation only in mice, rats, gerbils and hamsters. The mechanism governing de novo DNA methylation in the oocytes of most mammalian species, including humans, occurs through a yet unknown mechanism that differs from the current model discovered in mouse.